2023
DOI: 10.1186/s12889-023-15235-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific effects on adverse pregnancy outcomes vary by maternal characteristics: a population-based retrospective study in Xiamen, China

Abstract: Background Advanced maternal age (AMA; ≥35 years) is considered to be a major risk factor for adverse pregnancy outcomes. Along with the global trend of delayed childbearing, and in particular, the implementation of China’s second and third-child policy leading to a dramatic increase of AMA in recent years, the association between maternal age and pregnancy outcomes requires more investigation. Methods A population-based retrospective study was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…One possible explanation for this finding is that younger mothers may have higher metabolic rates and energy needs than older mothers, which may result in increased food intake and weight gain. This hypothesis is supported by previous studies that have shown that maternal age is inversely related to basal metabolic rate and energy expenditure [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 85%
“…One possible explanation for this finding is that younger mothers may have higher metabolic rates and energy needs than older mothers, which may result in increased food intake and weight gain. This hypothesis is supported by previous studies that have shown that maternal age is inversely related to basal metabolic rate and energy expenditure [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 85%
“…The possible reason for the increase in premature births and infants with low birth weight could be due to the increase in women with advanced maternal age along with the changed fertility policy, as previous studies revealed that advanced maternal age was an established risk factor for premature birth and neonatal low birth weight. 40 41 The increased premature birth and low birth weight rates require additional attention in the clinical practice, both prepregnancy and antenatal counselling to the couples and follow-up care for these infants is needed.…”
Section: Discussionmentioning
confidence: 99%
“…. It was previously shown that mothers of AMA are at a higher risk of having their newborns transferred to the neonatal intensive care unit (NICU) [ 2 ]. The NICU is a medical facility primarily dedicated to the treatment of critically ill newborns within the first 28 days of life.…”
Section: Introductionmentioning
confidence: 99%